1990
DOI: 10.1093/ajcn/52.4.640
|View full text |Cite
|
Sign up to set email alerts
|

Reducing-diet and exercise-training effects on serum lipids and lipoproteins in mildly obese women

Abstract: Twenty-one mildly obese women were fed a 1268-kcal lactovegetarian diet for 5 wk. Subjects were randomly divided into either an exercise (Ex) or a nonexercise (Nex) group. The Ex group walked at 60% heart-rate reserve (134 +/- 2 bpm; mean +/- SEM) during 45-min sessions, five times per week. Although exercise improved estimated maximum oxygen consumption (VO2max; 20.9 +/- 3.2% vs 2.1 +/- 3.4% in Ex vs Nex, respectively), changes in total body, lean body, and fat weight did not differ significantly between grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0
5

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 30 publications
3
40
0
5
Order By: Relevance
“…Other studies with women utilizing more traditional modes of activity such as walking or running support our findings in regard to increased HDL-C concentration [22,27]. Typical HDL-C changes found in exercise studies with female subjects report average changes of 3 -5 mg/dl following training.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies with women utilizing more traditional modes of activity such as walking or running support our findings in regard to increased HDL-C concentration [22,27]. Typical HDL-C changes found in exercise studies with female subjects report average changes of 3 -5 mg/dl following training.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore we conducted the study to see whether acute exercise and/or a CAF, CAR, or CAF+CAR mixture trial affects blood TC, TG, and FFA levels. Aerobic exercise increases HDL-cholesterol with moderate exercise in obese women (51) and men (52), but other studies (53,54) have shown little or no effect on TC, TG, and LDL cholesterol. In our study, acute ex ercise increased TC, TG, and FFA levels, but a CAF and a CAR trial did not affect them (Table 4).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, these studies usually examine relations in individuals diverse in the amount and location of adiposity and rarely account for the potential that there might be differential effects in women with an upper-body versus a lower-body fat distribution. 10,20,[23][24][25][26] Although the relations derived from studies of this type are convincing, they must be tempered by the fact that these analyses are correlational rather than causal. Thus, the potential benefits of interventions that change WHR or BMI on CVD riskfactor status can only be surmised by extrapolation.…”
Section: Discussionmentioning
confidence: 99%